The Mediating Role of Product Quality in the Relationship Between Price and Marketing Performance of Small and Medium Enterprises in Ghana - Collins Kankam-Kwarteng; Francis Osei; Samuel Owusu-Mensah; Beverley Wilson-Wünsch (Research Synergy Foundation, 2025)
Small and Medium Enterprises (SMEs) play a critical role in Ghana’s economic growth, employment generation, and poverty reduction, yet they encounter significant hurdles in enhancing their marketing performance. With pricing strategies and product quality recognized as pivotal factors in gaining a competitive edge, this study investigates the relationships among price, product quality, and marketing performance in Ghanaian SMEs. The study targeted 100 owner-managers selected through convenience and purposive sampling, and data were analyzed using SMART PLS version 3.0 and SPSS version 25, applying the partial least squares structural equation modeling (PLS-SEM) technique to test the proposed model and hypotheses. Findings reveal a notable positive association between price and marketing performance, underscoring the strategic importance of effective pricing. Additionally, a strong relationship between pricing and product quality was found, emphasizing the need for competitive pricing to support superior product quality. This study also identifies the significant role of product quality in enhancing marketing performance. Importantly, the analysis reveals that product quality mediates the relationship between price and marketing performance, providing new insights into SME dynamics. Based on these results, it is recommended that Ghana’s SMEs pursue a coordinated approach to pricing and quality management. By aligning competitive pricing with a commitment to high-quality product delivery, SMEs can drive customer satisfaction, foster loyalty, and achieve sustainable profitability, thereby improving their overall marketing performance in a competitive landscape.